Bio-nanoparticle assembly: a potent on-site biolarvicidal agent against mosquito vectors. Issue 16 (5th March 2020) - Sultana, Nazima; Raul, Prasanta K.; Goswami, Diganta; Das, Dipankar; Islam, Saidul; Tyagi, Varun; Das, Bodhaditya; Gogoi, Hemanta K.; Chattopadhyay, Pronobesh; Raju, Pakalapati S.
Abstract : The present work demonstrates a potent and stable biolarvicidal agent using sustainable bioresources. The synthesized nanomaterials can control the mosquito vectors at a very low concentration range (0.01–1.00 mg L −1 ) for on-site field applications. Abstract : Background : Vector-borne diseases such as malaria, dengue, yellow fever, encephalitis and filariasis are considered serious human health concerns in the field of medical entomology. Controlling the population of mosquito vectors is one of the best strategies for combating such vector-borne diseases. However, the use of synthetic insecticides for longer periods of time increases mosquito resistance to the insecticides. Recently, the search for new environmentally friendly and efficient insecticides has attracted major attention globally. With the evolution of material sciences, researchers have reported the effective control of such diseases using various sustainable resources. The present investigation demonstrates a potent on-site biolarvicidal agent against different mosquito vectors such as Aedes albopictus, Anopheles stephensi and Culex quinquefasciatus . Methods : Stable and photo-induced colloidal silver nanoparticles were generated via the surface functionalization of the root extract of Cyprus rotundas . Characterizations of the nanoparticles were performed using assorted techniques, such as UV-visible spectroscopy, FTIR spectroscopy, DLS and HRTEM. The bioefficacy of the synthesized nanoparticles was investigated against different species of mosquito larvae through the evaluation of their life history trait studies, fecundity and hatchability rate of the treated larvae. Histopathological and polymerase chain reaction-random amplified polymorphic DNA (RAPD) analyses of the treated larvae were also examined to establish the cellular damage. Results : The synthesized nanoparticles showed remarkable larvicidal activity against mosquito larvae in a very low concentration range (0.001–1.00) mg L −1 . The histopathological study confirmed that the present nanoparticles could easily enter the cuticle membrane of mosquito larvae and subsequently obliterate their complete intestinal system. Furthermore, RAPD analysis of the treated larvae could assess the damage of the DNA banding pattern. Conclusion : The present work demonstrates a potent biolarvicidal agent using sustainable bioresources of the aqueous Cyprus rotundas root extract. The results showed that the synthesized nanoparticles were stable under different physiological conditions such as temperature and photo-induced oxidation. The effectiveness of these materials against mosquito larvae was quantified at very low dose concentrations. The present biolarvicidal agent can be considered as an environmentally benign material to control the mosquito vectors with an immense potential for on-site field applications.